2019
DOI: 10.1515/erj-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Entrepreneurship and Economic Development. An Empirical Approach

Abstract: This paper investigates the influence of culture on the level of entrepreneurship and the possible moderating role of the level of economic development upon this relationship. For our purpose, an initial sample of 125 countries (43 high-income and 82 low-income countries) is used, over the 2006–2016 time period. At first, we use a panel analysis of the reduced sample which is furthermore completed by a hierarchical regression analysis. Our main results provide clear evidence that culture represents an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
4
20
1
Order By: Relevance
“…Regarding the context of the study in Finland, it is likely that one would observe different patterns in different countries as factors such as economic development and culture play a substantial role in the formation of occupational and entrepreneurial aspirations and its materialization in entrepreneurial action [137,138]. We note however that the present results are counter-intuitive.…”
Section: Discussion Of the Resultscontrasting
confidence: 65%
“…Regarding the context of the study in Finland, it is likely that one would observe different patterns in different countries as factors such as economic development and culture play a substantial role in the formation of occupational and entrepreneurial aspirations and its materialization in entrepreneurial action [137,138]. We note however that the present results are counter-intuitive.…”
Section: Discussion Of the Resultscontrasting
confidence: 65%
“…At the cultural level, however, no gender differences are observed; the entrepreneurial culture in Andalusia is perceived in the same way by men and women. In this regard, previous studies show contradictory results (Achim et al. , 2021; Shinnar et al.…”
Section: Discussionmentioning
confidence: 88%
“…, 2018). Then it incorporates the sociological approach, including the importance of context and culture in the social consideration of the entrepreneur and new business creation (Achim et al. , 2021; Steyaert and Katz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to Šanda and Křupka (2018), various regions possess different innovativeness abilities. These are often de ned by the region's characteristics, including the region's cultural diversity, population demographic, talent within the working individuals, and the wealth within the region's economy (Achim et al, 2021). Zul qar et al( 2019) also suggested that entrepreneurs must identify opportunities in society and the market to fuel entrepreneurial initiatives and economic stability.…”
Section: Theoretical Approachesmentioning
confidence: 99%